2009
DOI: 10.1002/lary.20191
|View full text |Cite
|
Sign up to set email alerts
|

Eotaxin‐1, ‐2, and ‐3 immunoreactivity and protein concentration in the nasal polyps of eosinophilic chronic rhinosinusitis patients

Abstract: Major causes of olfactory disorders are sinonasal disease, viral upper respiratory tract infection, head trauma and old age. Olfactory testing is an important part of objective assesment of the severity of the disease in chronic rhinosinusitis and nasal polyposis. The aim of this study was to correlate results of objective smell testing with subjective scores on olfaction and other nasal symptoms in different subgroups of patients with smell impairment.Data were extracted from questionnaires filled by patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 26 publications
3
60
1
Order By: Relevance
“…Eosinophil has a unique morphology in shape when the asthmatic event cause the number, therefore, we counted the numbers by comparing control and SoL-treated sample, as shown in detail with slight modifications (15).…”
Section: Il-4 Il-13 and Ige Levelsmentioning
confidence: 99%
“…Eosinophil has a unique morphology in shape when the asthmatic event cause the number, therefore, we counted the numbers by comparing control and SoL-treated sample, as shown in detail with slight modifications (15).…”
Section: Il-4 Il-13 and Ige Levelsmentioning
confidence: 99%
“…Normal T Expressed and Secreted) and eotaxin-2 are important recruiters and activators of eosinophils and have been postulated to be responsible for eosinophilia in the tissue stroma of the polyp [8][9][10][11][12][13][14][15][16][17][18] . About this matter, the interaction of chemokines with their receptors in CRS with NSP is important, with CCR-5 and CCR-3 being the receptors more extensively studied 19 .…”
Section: The Chemokines Rantes (Regulated On Activationmentioning
confidence: 99%
“…Currently, the exact reason for high eosinophil infiltration accompanied with a shift to a more Th2-typed response in eosinophilic CRSwNP patients is not fully understood. IL-5 and eotaxin are traditionally considered the key cytokines for the accumulation, survival and activation of eosinophils in polyp tissues [59,60]. Recently, our group, and others, demonstrated that osteopontin, a phosphorylated acidic glycoprotein, plays a critical role in the chemotaxis of eosinophil in eosinophilic CRSwNP [61 & ,62].…”
Section: The Implications Of Short Palate Lung and Nasal Epithelialmentioning
confidence: 99%